Moderasi Beragama Di Media Sosial Dalam Perspektif Teologi Kristen - Doma, Yabes (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
This article discusses the concept of religious moderation in the context of social media from the perspective of Christian theology. This emphasizes the importance of moderation in managing Indonesia's diverse religious landscape to prevent conflict and promote harmony. The article also explores the role of social media in facilitating interfaith dialogue, increasing empathy, and challenging negative stereotypes about religion. The report highlights the potential of social media in fostering understanding, tolerance, and cooperation among different faith communities. This article provides insight into the importance of utilizing social media as a tool for interfaith dialogue and understanding.